INOVASI DAN LAYANAN PRIMA PADA USAHA KERIPIK PISANG MF - Nurhidayah; Gautama, Budi (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
In a business, increasing production and service is very important for business progress through creativity and innovation. For MSME players, being creative in improving product quality, making innovations or new breakthroughs in products and improving services are things that will become strengths and ways to maintain business continuity, which will also help increase sales. As applied by the MF banana chips business which was established in 2017 and is located in Ujung Gurap, Padangsidimpuan, North Sumatra, it has succeeded in increasing the business turnover. With limited raw materials, few flavor variants, simple product packaging and mediocre service led this business to innovate. This study aims to determine product innovation and excellent service carried out by the MF banana chips business. This research is a type of qualitative research with data collection methods through interview and observation techniques and using a literature study approach. The results stated that the business owner (Mrs. Fahri) did creativity and innovation in her product, namely changing the type of raw material for banana chips and adding new flavors to her product. In addition, the MF banana chips business also provides excellent service through convenience, speed and hospitality through actions, where previously there were services that were not available.